Organizational sustainability: the role of environmentally focused practices in enhancing environmental performance—an emerging market perspective - Naveed R. Khan; Falak Malik; Mustafa Rehman Khan; Ismail Khan; Arsalan Mujahid Ghouri (Discover Sustainability)
Abstract This study aims to examine the impact of environmental transformational leadership through green human resource management (GHRM) and environmental management system on environmental performance (EP) in textile manufacturing firms. In this cross-sectional study, PLS-SEM method was used to analyze 244 responses collected from managers using purposive sampling. Our findings showed that environmental transformational leadership has a significant relationship with GHRM, environmental management system, and EP. Likewise, environmental management system has a significant relationship with EP. However, GHRM has an insignificant relationship with EP. Moreover, the environmental management system complementary mediates the relationship between environmental transformational leadership and EP. Meanwhile, GHRM insignificantly mediates the relationship between environmental transformational leadership and EP. Our study provides novel contribution by examining environmentally focused practices and organizational sustainability within an under-researched, emerging market context. We offer insights into how environmental transformational leadership and environmental management system addressing environmental challenges as outlined by the SDGs. Managers are suggested to regularly identify environmental issues relevant to the firm, communicate environmental requirements to suppliers, and implement environmental life cycle assessments to redesign products or manufacturing processes.